Sudden rupture of recurrent rectal prolapse complicated by small intestine evisceration from anus: a case study - Tian, Zhesen; Ma, Xiaopeng; Li, Mingda; Ruan, Hongxun; Zhang, Guojian; Zhao, Yalei (Frontiers in Medicine, 2025)
Evisceration of the small intestine from the anus is a rare complication following rectal injury. In patients with recurrent rectal prolapse, delayed surgical intervention can lead to rectal wall thinning due to chronic ischemia, increasing the risk of rectal rupture and subsequent intrusion of the small bowel followed by antegrade intussusception. Since Bodie first described this condition in 1827, fewer than one hundred cases have been reported globally. This case involved a 78-year-old male with a 60-year history of untreated rectal prolapse. After a fall, his abdominal pressure increased abruptly, causing rectal rupture and intussusception of the small intestine through the anus. An emergency Hartmann procedure was performed, and the patient recovered well. This case underscores the need for early surgical intervention in chronic rectal prolapse to prevent severe complications. It also highlights the unique mechanism of rectal injury under external force, providing valuable insights for managing similar complex cases.